2016
DOI: 10.1097/igc.0000000000000751
|View full text |Cite
|
Sign up to set email alerts
|

How Common Is the Growing Teratoma Syndrome in Patients With Ovarian Immature Teratoma?

Abstract: The development of GTS after adjuvant chemotherapy for ovarian IT seems to be more common than previously reported in the literature. Clinicians need to be cognizant that the occurrence of rapidly growing masses during or after chemotherapy for ovarian IT raises the possibility of GTS. This highlights the importance of prolonged follow-up with tumor markers and imaging studies in patients with ovarian IT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 26 publications
0
28
0
3
Order By: Relevance
“…The median (range) interval between the diagnosis of ovarian immature teratoma and GTS has been reported to be nine (4-55) months ( 2 ). Although approximately 100 cases have been reported in the English literature, a recent article found that GTS is more common than previously reported, with an incidence of 40% in patients who had already undergone surgery ( 3 , 4 ). Mostly, it occurs in the pelvic region but there are also some patients with extra-pelvic disease, such as lung, mediastinum, central nervous system, spleen and diaphragm ( 5 , 6 , 7 ).…”
Section: Discussionmentioning
confidence: 95%
“…The median (range) interval between the diagnosis of ovarian immature teratoma and GTS has been reported to be nine (4-55) months ( 2 ). Although approximately 100 cases have been reported in the English literature, a recent article found that GTS is more common than previously reported, with an incidence of 40% in patients who had already undergone surgery ( 3 , 4 ). Mostly, it occurs in the pelvic region but there are also some patients with extra-pelvic disease, such as lung, mediastinum, central nervous system, spleen and diaphragm ( 5 , 6 , 7 ).…”
Section: Discussionmentioning
confidence: 95%
“…In humans, CR (mature teratomatous metastasis) was first reported in immature ovarian teratomas [ 8 ]; this phenomenon also occurs in disseminated or metastatic foci of malignant mixed germ cell tumors of the ovary and testis [ 28 , 29 ]. CR has also been termed “transformation”, “evolution”, or “growing teratoma syndrome” [ 28 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…dIscusIón Los teratomas inmaduros de ovario representan menos del 1% de los casos de cáncer de ovario, y son un tipo poco común de tumor de células germinales, afectando principalmente a muje-res jóvenes, con una edad diagnóstica promedio de 19 años. (6) En el Perú, la literatura es limitada pero se ha reportado este fenómeno en un caso de cáncer de testículo. (8) Estos casos suelen responder de manera favorable al tratamiento quirúrgico con resección total o parcial del tumor, seguido por quimioterapia con bleomicina, etopósido y cisplatino, dada su alta sensibilidad a la misma.…”
Section: Reporte De Casounclassified
“…El intervalo de presentación entre el tumor inicial y el STC varía desde 4 hasta 55 meses aproximadamente, con una mediana de 9 meses, habiendo reportes desde el segundo ciclo de quimioterapia, como hasta 12 años después el diagnóstico inicial. Sin embargo, la mayoría de los casos se presentan en los primeros dos años, por lo que la posibilidad de una recurrencia debe estar presente, como se mencionó anteriormente (6) . En el caso de nuestra paciente, la aparición de nuevas lesiones ocurrió 1 años después del fin de la quimioterapia, y la ubicación fue confinada al peritoneo.…”
Section: Reporte De Casounclassified
See 1 more Smart Citation